Improved the Speed Up Time and Accuracy Training in the Batch Back Propagation Algorithm via Significant Parameter - Sarhan Al_Duais, Mohammed; Susilawati Mohamad, Fatma; Mohamad, Mumtazimah (International Journal of Engineering and Technology, 2018)
Although the batch backpropagation (BBP) algorithm is a new style for weight updating, it is slow training and there are several parameters that needed to be adjusted manually. The most significant parameter for improving the efficiency of the batch back propagation algorithm is learning rate. The drawbacks of the BBP algorithm are its slow learning rate and easy convergence to the local minimum. To overcome this problem, we have created a new dynamic learning rate (LR) to escape the local minimum, which enables a faster training time for the batch back propagation algorithm. The dynamic batch backpropagation (DBBPL) algorithm, which uses this dynamic learning rate, is presented in this paper. This technique was implemented using a sigmoid function, and the two-dimensional exclusive OR problem, the balance dataset, and the Iris dataset were used as benchmarks with different structures to test the efficiency of the dynamic learning rate. The real datasets were divided into a training set and a testing set. 75 experiments were carried out using MATLAB software (2012a). From the experimental results, the DBBPL algorithm provides superior performance in terms of training and quickly training with the high level of accuracy compared to the BBP algorithm,Â whereas the accuracy rates of the structures were 98.7% and 99.1%, and processing times of the improved algorithm were 3936 and 4755 times faster, respectively than the BBP algorithm, and with existing works. Â Â